KAJIAN KELAYAKAN WATER FRONT CITY KABUPATEN MALUKU TENGGARA, PROVINSI MALUKU - Berhitu, Pieter Thomas; Boreel, Aryanto; Botanri, Adnan Affan Akbar (CENDEKIA: Jurnal Ilmu Pengetahuan, 2025)
Coastal development in Indonesia is receiving increasing attention as the need for urban spaces oriented towards sustainability, comfort, and aesthetics increases. One relevant approach is the Waterfront City (WFC) concept, a coastal-based city development that integrates ecological, social, cultural, and economic aspects. This study aims to assess the feasibility of developing a Waterfront City in Southeast Maluku Regency by assessing the area's existing conditions, social potential, and economic prospects. The research method uses a descriptive-analytical approach through a combination of secondary data in the form of regional planning documents and primary data from field surveys, interviews, and questionnaires. The analysis is conducted based on social, economic, technical, and environmental aspects to obtain a comprehensive picture. The results show that the coastal area of ??Langgur City, particularly Watdek, Ohoijang, and Tanah Misi, faces pressure due to dense settlements above the sea, environmental degradation, and limited basic infrastructure. From a social perspective, the majority of the community supports waterfront development in the hope of increasing public space, tourist access, and new job opportunities, despite concerns regarding the relocation of traditional settlements. Local cultural factors, such as Larvul Ngabal and the principle of ain ni ain, serve as important social capital in encouraging community acceptance. From an economic perspective, the feasibility analysis shows a positive NPV, high IRR, and a B/C ratio >1, indicating that the project is financially viable. Overall, the development of Waterfront City in Southeast Maluku is considered feasible if designed in a participatory manner and based on sustainable development principles. The project's success is largely determined by the integration of spatial planning policies, community involvement, and efforts to maintain a balance between economic growth, cultural preservation, and coastal environmental sustainability. ABSTRAKPembangunan kawasan pesisir di Indonesia semakin mendapat perhatian seiring meningkatnya kebutuhan ruang kota yang berorientasi pada keberlanjutan, kenyamanan, dan estetika. Salah satu pendekatan yang relevan adalah konsep Waterfront City (WFC), yaitu pengembangan kota berbasis pesisir yang mengintegrasikan aspek ekologis, sosial, budaya, dan ekonomi secara terpadu. Penelitian ini bertujuan untuk mengkaji kelayakan pembangunan Waterfront City di Kabupaten Maluku Tenggara dengan menilai kondisi eksisting kawasan, potensi sosial, serta prospek ekonomi. Metode penelitian menggunakan pendekatan deskriptif-analitis melalui kombinasi data sekunder berupa dokumen perencanaan daerah dan data primer dari survei lapangan, wawancara, serta kuesioner. Analisis dilakukan berdasarkan aspek sosial, ekonomi, teknis, dan lingkungan untuk memperoleh gambaran komprehensif. Hasil penelitian menunjukkan bahwa kawasan pesisir Kota Langgur, khususnya Watdek, Ohoijang, dan Tanah Misi, menghadapi tekanan akibat padatnya permukiman di atas laut, degradasi kualitas lingkungan, serta keterbatasan infrastruktur dasar. Dari sisi sosial, mayoritas masyarakat mendukung pembangunan waterfront dengan harapan meningkatnya ruang publik, akses wisata, dan lapangan kerja baru, meskipun terdapat kekhawatiran terkait relokasi permukiman tradisional. Faktor budaya lokal, seperti Larvul Ngabal dan prinsip ain ni ain, menjadi modal sosial penting dalam mendorong penerimaan masyarakat. Dari sisi ekonomi, analisis kelayakan menunjukkan nilai NPV positif, IRR tinggi, dan B/C ratio > 1, menandakan bahwa proyek ini layak secara finansial. Secara keseluruhan, pengembangan Waterfront City di Maluku Tenggara dinilai feasible apabila dirancang secara partisipatif dan berlandaskan prinsip pembangunan berkelanjutan. Keberhasilan proyek ini sangat ditentukan oleh integrasi kebijakan tata ruang, keterlibatan masyarakat, serta upaya menjaga keseimbangan antara pertumbuhan ekonomi, pelestarian budaya, dan kelestarian lingkungan pesisir.